Occupational Stress among Health Professional during Covid-19 Pandemic - Supratman, S; Mastuti, Dewi; Widodo, Arif; Rosyid, Fahrun Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: This study aim was to describe occupational stress among health professional staff during Covid-19 pandemic at Baki Community Health Center (puskesmas), Distric of Sukoharjo, Jawa Tengah, Indonesia. Methodology: The study employed a descriptive survey design. The study population was enlisted from Community Health Centre (puskesmas) Kecamatan Baki, District of Sukoharjo. They were employing a total of 54 health professional include physicians, nurses and midwives. A questionnaire was administered in November 2020. There were 54 health professionals and we received consecutively completed responses. An instrument - Perceived Stress Scale - were used for data collection. The stressors were divided in to those that were related to health, those that were psychosocial in nature and those that were related to work environment.Results: Physicians were the most health professional feeling stress compared to nurses and midwives (33.3%). Again males participant were more stress than female health professional (28.6%). They are age less than 40 years old mostly stressful compare to more age (45.9%). From all respondents who has work experience less than 10 year are more stress than others (33.3%).Applications/Originality/Value: This study was an investigation during pandemic Covid-19 related to stress among health care workers in Indonesia. It can be seen that the study could to provide valuable contribution to promote mental health problems among health professional.